2018
DOI: 10.1063/1.5026147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of threading dislocation density on the lifetime of InAs quantum dot lasers on Si

Abstract: We investigate the impact of threading dislocation density on the reliability of 1.3 lm InAs quantum dot lasers epitaxially grown on Si. A reduction in the threading dislocation density from 2.8 Â 10 8 cm À2 to 7.3 Â 10 6 cm À2 has improved the laser lifetime by about five orders of magnitude when aged continuous-wave near room temperature (35 C). We have achieved extrapolated lifetimes (time to double initial threshold) more than 10 Â 10 6 h. An accelerated laser aging test at an elevated temperature (60 C) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 25 publications
8
77
0
1
Order By: Relevance
“…5(d), since the high BL and WL carrier loss rate manifests itself effectively in a reduced injection efficiency into the QDs. These results agree with the experimentally observed trends reported by Jung et al and Orchard et al [30,40]. It is, however, likely that the modelled slope decrease is even underestimated, since a very high TD density will also lead to dislocation-induced optical losses, as indicated in Ref.…”
Section: Qd Parameters Qw Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…5(d), since the high BL and WL carrier loss rate manifests itself effectively in a reduced injection efficiency into the QDs. These results agree with the experimentally observed trends reported by Jung et al and Orchard et al [30,40]. It is, however, likely that the modelled slope decrease is even underestimated, since a very high TD density will also lead to dislocation-induced optical losses, as indicated in Ref.…”
Section: Qd Parameters Qw Parameterssupporting
confidence: 92%
“…40. Despite the performance reduction observed at higher values of ρdis, our theoretical results support the hypothesis that the unique properties of QDs, efficient carrier capture and high carrier confinement, are key to the impressive capabilities of QD lasers on Si to operate under high TD densities [30,32]. It should be noted that our model does not contain thermal effects, so it is not considered that the possibility of overcoming the laser threshold may be reduced at increased injection levels.…”
Section: Qd Parameters Qw Parameterssupporting
confidence: 60%
See 1 more Smart Citation
“…This analysis suggests that we might expect the degradation rate in quantum dot lasers to be related to the carrier density at threshold, which is itself related to the gain requirement or total optical loss. Recent measurements [18] have shown that the degradation rate is lower in p-modulation doped quantum dot lasers grown on silicon and in this case the electron and hole quasi-Fermi levels are both moved towards the valence states [19] reducing the electron population able to access the 2D states, also supporting the argument that the carrier density populating the extended states, and thus able to access the defects, is critical in addition to the number of defects present.…”
supporting
confidence: 53%
“…With careful device and contact mask design, we propose that ECCI could even be used to track dislocation evolution in operando. This is a fascinating opportunity to explore the failure mechanisms of semiconductor devices such as GaAs/Si quantum dot lasers [37,38] and GaN [39] and SiC [40] power devices where carrier recombination or electric field-induced dislocation motion is suspected or has been observed postdegradation.…”
mentioning
confidence: 99%